NGO’s Roles and Strategies in the Environmental Politic Arena - Ardhian, David; Adiwibowo, Soeryo; Sri Wahyuni, Ekawati (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTNGOs have played increasingly prominent roles and strategies in the environment politic arena. The study was carried out using qualitative approach at national and local to elaborate Indonesia NGOs roles and strategies in responding land and forest fires. The Study reveals that NGOs were be able to take advance of collective deprivations and political opportunities to develop mobilization structure, framing process and various form of actions in responding land and forest fires. NGOs political strategies are directly influence key stakeholders,develop pressure to governmnet using transnational advocacy networks, enhancing market and sustainability standart to private sectors, influencing capital flow, mobilizing elits and promoting best practices at local as alternative solutions. NGOs plays as social movement organization in the frame of new social movement to enhance the equality of power relations, through influencing policies, law enforcement, market and private sectors behaviour, and promoting community-based peatland management model at local, toward better governance of natural resources management in Indonesia.Keywords : NGO, social movement, political ecology, land and forest fireABSTRAKOganisasi Non Pemerintah (ORNOP) memainkan peran dan strategi penting dalam arena politik lingkungan hidup. Studi dilakukan dengan pendekatan kualitatif untuk menjelaskan peran dan strategi ORNOP di Indonesia pada tingkat nasional dan lokal dalam menanggapi kasus kebakaran hutan dan lahan. Studi mengungkap bahwa ORNOP mampu memanfaatkan keluhan kolektif dan struktur kesempatan politik untuk membangun struktur mobilisasi, proses framing dan bentuk-bentuk aksi. Strategi Politik ORNOP diwujudkan dengan cara mempengaruhi secara langsung pihak-pihak kunci, meningkatkan tekanan politik terhadap pemerintah dengan menggunakan jaringan advokasi lintas negara, mendorong standar keberlanjutan pasar, mempengaruhi aliran kapital, mobilisasi dukungan elit dan mempromosikan praktik-praktik terbaik sebagai solusi tandingan. ORNOP mampu memainkan peran sebagai organisasi gerakan sosial untuk mendorong kesetaraan relasi kuasa, dengan mempengaruhi kebijakan, penegakan hukum, perilaku pasar dan sektor swasta, serta mempromosikan pengelolaan lahan gambut berbasis masyarakat pada tingkat lokal, dalam rangka penguatan tata kelola sumberdaya alam di Indonesia.Kata kunci : organisasi non pemerintah, gerakan sosial, ekologi politik, kebakaran hutan dan lahan